Exploring Autism : A Conversation with Uta Frith. - Burton, Howard (Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and one of the world's leading experts on autism Uta Frith, Professor of Cognitive Development at University College London. Topics that are examined in this extensive conversation are what autism actually is, the reasons behind the increased number of diagnoses over the last few years, autism spectrum disorders, Asperger's syndrome, mentalizing, brain imaging to research the cognitive and neurobiological bases of autism and more.This carefully-edited book includes an introduction, The Autistic Condition, and questions.
Description based upon print version of record.
Keywords: Frith, Uta -- Interviews.; Autism.; Autistic Disorder; Autisme.; Child.; Developmental.; PSYCHOLOGY.; Autism Spectrum Disorders.; Psychopathology.; Social Psychology.; Cognitive Neuroscience & Cognitive Neuropsychology.; FAMILY & RELATIONSHIPS.; Autism; Interviews